British Public Service Broadcasting, the EU and Brexit. (18th November 2021) - Berry, Mike; Wahl-Jorgensen, Karin; Garcia-Blanco, Inaki; Bennett, Lucy; Cable, Joe
ABSTRACT: This paper analyses the historic role of Britain's major public service broadcaster, the BBC, in reporting the European Union. To do this it combines a content analysis of two datasets of BBC broadcast and online coverage from 2007 and 2012 with a series of semi-structured interviews conducted with former and current senior BBC editors and journalists. The research finds that BBC coverage in the pre-referendum period was closely tied to major events – such as summits – and elite party conflict. These patterns in coverage were primarily a consequence of the lack of traditional news values inherent in most EU stories and the impact of the wider political and media landscape. The consequence of these patterns in coverage was to present audiences with a restricted, negative and largely conflictual picture of Britain's relationship with the EU which is likely to have fuelled rather than inhibited the growth of Euroscepticism.